Design and fabrication of miniaturized PEM fuel cell combined microreactor with self-regulated hydrogen mechanism. (November 2015) - Balakrishnan, A; Frei, M; Kerzenmacher, S; Reinecke, H; Mueller, C
Abstract: In this work we present the design and fabrication of the miniaturized PEM fuel cell combined microreactor system with hydrogen regulation mechanism and testing of prototype microreactor. The system consists of two components (i) fuel cell component and (ii) microreactor component. The fuel cell component represents the miniaturized PEM fuel cell system (combination of screen printed fuel cell assembly and an on-board hydrogen storage medium). Hydrogen production based on catalytic hydrolysis of chemical hydride takes place in the microreactor component. The self-regulated hydrogen mechanism based on the gaseous hydrogen produced from the catalytic hydrolysis of sodium borohydride (NaBH4 ) gets accumulated as bubbles at the vicinity of the hydrophobic coated hydrogen exhaust holes. When the built up hydrogen bubbles pressure exceeds the burst pressure at the hydrogen exhaust holes the bubble collapses. This collapse causes a surge of fresh NaBH4 solution onto the catalyst surface leading to the removal of the reaction by-products formed at the active sites of the catalyst. The catalyst used in the system is platinum deposited on a base substrate. Nickel foam, carbon porous medium (CPM) and ceramic plate were selected as candidates for base substrate for developing a robust catalyst surface. For the first time the platinum layer fabricated by pulsed electrodeposition and dealloying (EPDD) technique is used for hydrolysis of NaBH4 . The major advantages of such platinum catalyst layers are its high surface area and their mechanical stability. Prototype microreactor system with self-regulated hydrogen mechanism is demonstrated.